Talking Cyberwar: Does Commitment to the Global Cybersecurity Agenda indicate Cyberthreat Readiness? - Ada PETER; Tolulope KAYODE-ADEDEJI; Esther OMEMU (Communications of International Proceedings, 2021)
The increasing pitched battle between nations, governments, cyber warriors, and corporations is now glaring. For some countries, cyber weapons serve as deterrence to non-allies perceived as adversaries. David Sanger describes the cyberweapons used in these battles as the perfect weapon. Other common cyberweapons include espionage, denial-of-service, distributed denial-of-service, man-in-the-middle, phishing, spear-phishing, drive-by-attacks, password, SQL injection, eavesdropping attacks, malware attacks, birthday attacks, and all sorts of espionage. To raise awareness of these weapons and to foster a global culture of cybersecurity, the International Telecommunication Union (ITU) conducts a Global Cybersecurity survey. First launched in 2014 to raise awareness, the survey measured the commitment of Member States to cybersecurity. The second iteration in 2017 estimated the commitment of ITU Member States to cybersecurity to drive further efforts in the adoption and integration of cybersecurity on a global scale. But is a high or low measure of commitment an indicator for safety in the face of burgeoning cyber-attacks? Is a weak or strong commitment proportional to the rate of vulnerability, network attacks, web threats, ransomware, local infections, and spam? What does commitment mean? Are leading performers prone to fewer cyber threats? Is there a correlation between each nation's commitment, the rate of cyber threats, and how much it chants cyberwar on media outlets?
Keywords: Cyberwar; Cyberthreat; Global Cybersecurity Agenda (GCA); Media